Public health for children - DeBell, Diane (CRC Press, Taylor & Francis Group, 2016)
Following radical changes in public health provision, this book examines the implications for children and young adults as well as for those who provide care, prevention, and health promotion services. It also explores the challenges created by these significant structural and functional changes. Written by experts in the field, each chapter takes a practical approach to support learning and teaching.